2022
DOI: 10.1186/s40486-022-00156-5
|View full text |Cite
|
Sign up to set email alerts
|

Methods to analyze extracellular vesicles at single particle level

Abstract: Extracellular vesicles (EVs) are nano-sized vesicles derived from cells that transport biomaterials between cells through biofluids. Due to their biological role and components, they are considered as potential drug carriers and for diagnostic applications. Today's advanced nanotechnology enables single-particle-level analysis that was difficult in the past due to its small size below the diffraction limit. Single EV analysis reveals the heterogeneity of EVs, which could not be discovered by various ensemble a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…Similar to NTA, DLS is also a well-established technique based on the Brownian motion of suspended particles that is commonly used for the analysis of miEVs size distribution and surface charge . Using this method, researchers found that infection of bovines with leukemia virus has no remarkable effect on isolated miEVs size distribution .…”
Section: Characterization Of Mievsmentioning
confidence: 99%
“…Similar to NTA, DLS is also a well-established technique based on the Brownian motion of suspended particles that is commonly used for the analysis of miEVs size distribution and surface charge . Using this method, researchers found that infection of bovines with leukemia virus has no remarkable effect on isolated miEVs size distribution .…”
Section: Characterization Of Mievsmentioning
confidence: 99%
“…To more sensitively, precisely, and quantitatively detect, monitor, and investigate cancer EVs, EVs need to be analyzed at the single vesicle level. Different single vesicle technologies have been reported in recent years [ 204 ]. We expect nanomaterials will play a rapidly increasing role in the development of new SVTs for EV protein and nucleic acid detection and profiling, for basic vesicle research and clinical applications.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…27 Recent technological advances have also demonstrated EV-based diagnosis for cancer, 28–30 Alzheimer's disease 31 and Parkinson's disease 32 with superior detection sensitivity to conventional testing methods. Due to their nanoscale sizes (∼50 nm–1 μm), 33 EV isolation remains a major bottleneck and researchers are actively developing novel tools and assays to study EV biology and improve their clinical adoption.…”
Section: Introductionmentioning
confidence: 99%